Analisis Kebutuhan Perlengkapan Perkuliahan Menggunakan Metode Peramalan Dengan Mempertimbangkan Safety Stock Di Universitas X - Hasan, Fuad; Sutrisno, Sutrisno; Siregar, Ninny (Jurnal Ilmiah Teknik Mesin & Industri (JITMI), 2022)
Universitas X, which is a private university, annually accepts new student registrations with fluctuating numbers over the last 10 years. The supply of lecture equipment did not match the number of new students who registered. Therefore, it is necessary to forecast the number of new students in the future, so that the supply of lecture equipment can be met. The purpose of this study is to determine the need for new student lecture equipment for the coming year using the double exponential smoothing forecasting method, find out the level of safety stock for the lecture equipment needs for the coming year, knowing the amount of inventory for lecture equipment using the forecasting method taking into account the safety stock in the coming year. The forecasting method used was the Double Exponential Smoothing method and determined safety stock as the safety stock for lecture equipment. The results showed that number of student for A.Y 2021/2022 was 2374 people and for A.Y 2022/2023 was 2.424 people with a total safety stock of 710 bukus. With a service level of 90%, the total supply of manuals for A.Y 2021/2022 is 3.084 bukus and for A.Y 2022/2023 was 3.134 bukus.